Engineering design, planning, and management - Jack, Hugh (Academic Press, 2022)
Engineering Design, Planning and Management, Second Edition represents a compilation of essential resources, methods, materials and knowledge developed by the author and used over two decades. The book covers engineering design methodology through an interdisciplinary approach, with concise discussions and a visual format. It explores project management and creative design in the context of both established companies and entrepreneurial start-ups. Readers will discover the usefulness of the design process model through practical examples and applications from across engineering disciplines. Sections explain useful design techniques, including concept mapping and weighted decision matrices that are supported with extensive graphics, flowcharts and accompanying interactive templates. Discussions are organized around 12 chapters dealing with topics such design concepts and embodiments, decision-making, finance, budgets, purchasing, bidding, communication, meetings and presentations, reliability and system design, manufacturing design and mechanical design.